2009
DOI: 10.1111/j.1751-7141.2009.00028.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of an Electronic Medical Record to Characterize Cases of Intermediate Statin‐Induced Muscle Toxicity

Abstract: Statin use can be accompanied by a variety of musculoskeletal complaints. We describe the clinical characteristics of case subjects experiencing adverse statin-induced musculoskeletal symptoms within a large, population based cohort in Central Wisconsin. Case status was determined based upon elevated serum creatine kinase (CK) levels and the presence of at least one physician note reflecting an increased index of suspicion for statin intolerance. From the medical records of nearly 2 million unique patients, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…Notably, a direct comparison of the patient characteristics in our study to the Mangravite et al (2013) study is not possible with the available published data. A few patient characteristics can be found in the original Marshfield (Mareedu et al, 2009) and SEARCH (SEARCH Collaborative Group et al, 2008) publications for the overall patient samples, but the characteristics of the sub-groups used specifically in the Mangravite et al (2013) analysis are unavailable. However some notable differences between our study and the overall Marshfield and SEARCH studies include the statin treatment (our study is the only one to include rosuvastatin) and gender (the SEARCH trial was 83% male).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, a direct comparison of the patient characteristics in our study to the Mangravite et al (2013) study is not possible with the available published data. A few patient characteristics can be found in the original Marshfield (Mareedu et al, 2009) and SEARCH (SEARCH Collaborative Group et al, 2008) publications for the overall patient samples, but the characteristics of the sub-groups used specifically in the Mangravite et al (2013) analysis are unavailable. However some notable differences between our study and the overall Marshfield and SEARCH studies include the statin treatment (our study is the only one to include rosuvastatin) and gender (the SEARCH trial was 83% male).…”
Section: Discussionmentioning
confidence: 99%
“…There is wide phenotypic variability in the clinical manifestation of muscle toxicity for several orally administered medications such as HMG-CoA reductase inhibitors (statins) [57, 58]. Efforts are being made to standardize the clinical definition of these traits [59], and automated decision support is being deployed in the context of routine clinical practice to identify patients at risk [60].…”
Section: Ryr1 Pharmacogeneticsmentioning
confidence: 99%
“…Efforts are being made to standardize the clinical definition of these traits [59], and automated decision support is being deployed in the context of routine clinical practice to identify patients at risk [60]. For example, a study of statin-exposed patients identified 2,227 individuals with creatine kinase (CK) levels in the upper 10th percentile from among ~2 million unique patients by scanning electronic medical records [57]. Further exploratory analyses using a pathway-based approach have suggested that variants in multiple members of the RYR gene family may alter patient risk for statin-associated myopathy [61, 62].…”
Section: Ryr1 Pharmacogeneticsmentioning
confidence: 99%
“…Reduced GATM expression should reduce creatine synthesis. Furthermore, the relationship between the GATM differential eQTL locus expression with simvastatin exposure and statin-induced myopathy was examined in two separate population-based cohorts comprising 172 cases of myopathy (Link et al, 2008; Mareedu et al, 2009). Calculation of an odds ratio to quantify the association between presence of the rs9806699 variant and statin myopathy resulted in an overall odds ratio of 0.60 (95% confidence interval = 0.45–0.81) with meta-analysis of these two cohorts, suggesting that reduced GATM expression, and probable reduced creatine synthesis, is associated with a reduced incidence of statin-induced myopathy.…”
mentioning
confidence: 99%
“…No prior studies, including several genome-wide association studies (GWAS) (Link et al, 2008; Ruano et al, 2011), have identified the GATM gene as a contributor to statin myopathy. In the study by Mangravite et al (Mangravite et al, 2013), statin myopathy in their cohorts was defined by CK elevations 3–10 times the upper normal limits (Link et al, 2008; Mareedu et al, 2009). But perhaps the rs9806699 variant has indirect effects on CK levels that are independent of myopathy.…”
mentioning
confidence: 99%